New General Models for Evaluating Interactions in Non-Regular Solutions and Adsorption Energies Based on Both Hansen’s and Drago’s Parameters - Buchmann, Michel; Ho, Nam-Tran; Lamartine, Roger; Bonnamour, Isabelle (Journal of Applied Solution Chemistry and Modeling, 2016)
This study aims at providing a model for the internal mixing energy of two liquids. The concerned variables are the solute molar volume V (cm3/mol.), the cohesion parameters and the Drago’s parameters. The model is based on the following fundamental novelties: The fragmentation of molar cohesive energy ∆Ecoh (kJ/mol) into two distinct categories. Indeed, the dispersive and polar cohesion energies are magnetic and electrical in nature, and the cohesive energy of the chemical bonds (Hydrogen Bond) is due to charge transfer and orbital overlap. The origins of these two categories of energy are different, requiring two different treatments in use. For the first time, a relationship has been established between the cohesive energy from chemical bonds ∆Eh (kJ/mol) and Drago’s parameters Ea, Eb, Ca, and Cb (KJ1/ 2mol-1/2). A simple equation has been proposed for the salvation energy of a gaseous solute in a liquid solvent. This equation contains a term for the perturbation energy of the solvent in the presence of the solute, namely the cavity formation energy, and different types of interaction energies between the solvent and the solute at infinite dilution. Based on calorimetric data published, the proposed model is compared with the classic model in terms of the mixing energy. The result shows a clear advantage of the new model over the old or conventional one. Clearly, this new model should provide a new method to determine the interaction parameters or interaction capacities of complex pharmaceutical molecules using a series of simple and well-chosen solvents.